Ebolavirus: Comparison of Survivor Immunology and Animal Models in the Search for a Correlate of Protection - Longet, Stephanie; Mellors, Jack; Carroll, Miles W.; Tipton, Tom (Frontiers in Immunology, 2021)
Ebola viruses are enveloped, single-stranded RNA viruses belonging to the Filoviridae family and can cause Ebola virus disease (EVD), a serious haemorrhagic illness with up to 90% mortality. The disease was first detected in Zaire (currently the Democratic Republic of Congo) in 1976. Since its discovery, Ebola virus has caused sporadic outbreaks in Africa and was responsible for the largest 2013–2016 EVD epidemic in West Africa, which resulted in more than 28,600 cases and over 11,300 deaths. This epidemic strengthened international scientific efforts to contain the virus and develop therapeutics and vaccines. Immunology studies in animal models and survivors, as well as clinical trials have been crucial to understand Ebola virus pathogenesis and host immune responses, which has supported vaccine development. This review discusses the major findings that have emerged from animal models, studies in survivors and vaccine clinical trials and explains how these investigations have helped in the search for a correlate of protection.